1992
DOI: 10.1590/s0074-02761992000800042
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-treatment immunodiagnostic evaluation in human schistosomiasis mansoni

Abstract: Schistosomiasis control seems to be different in countries were low parasitic burden and asymptomatic clinical patients are the features of majority of cases. Immunological methods must substitute the traditional coprologic techniques used for some decades in the Control Program. Circumoval Precipitin Test (COPT), intradermal test and ELISA with soluble egg antigen (SEA) are evaluated for using as tools for seroepidemiologic studies. COPT and ELISA were performed after treatment to known their utility when imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…The gold standard diagnostic test: the circummoval precipitine test (COPT) -Based on the low sensitivity obtained (Mott & Cline 1980) by the classical Kato-Katz (Katz et al 1972) in areas of low transmission, the COPT (Oliver-González 1954) revealed the best performance, reaching a range of sensitivity of 92-100% and specificity of 96-100% (Spencer et al 1991, Alarcón de Noya et al 1992a). Purified S. mansoni eggs were incubated with patients sera for 48 h at 37°C.…”
Section: Evolution Of the Sampling And Serodiagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gold standard diagnostic test: the circummoval precipitine test (COPT) -Based on the low sensitivity obtained (Mott & Cline 1980) by the classical Kato-Katz (Katz et al 1972) in areas of low transmission, the COPT (Oliver-González 1954) revealed the best performance, reaching a range of sensitivity of 92-100% and specificity of 96-100% (Spencer et al 1991, Alarcón de Noya et al 1992a). Purified S. mansoni eggs were incubated with patients sera for 48 h at 37°C.…”
Section: Evolution Of the Sampling And Serodiagnostic Methodsmentioning
confidence: 99%
“…Additionally, it is the only test based on the detection of antibodies that correlates with parasite activity (Hillyer et al 1979). Antibodies against the excretory-secretory antigens released by eggs, starts to decline three months after successful chemotherapy (Alarcón de Noya et al 1992a).…”
Section: Evolution Of the Sampling And Serodiagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COPT, in spite of its high sensitivity and specificity, and its correlation with oviposition, remains only as a confirmatory diagnostic test, because it is very laborious and depends on ongoing life cycle . COPT value decreases slowly after treatment, becoming negative from six months to one year after effective chemotherapy (Alarcón de Noya et al 1992a).…”
Section: Schistosomiasis Applied Diagnosis In Venezuelamentioning
confidence: 99%
“…COPT continues to be our gold standard technique due to its high sensitivity, specificity and correlation with active cases (Alarcón de Noya et al 1992d). The COPT prevalence in cross-sectional studies is shown in Table III.…”
Section: Schistosomiasis In Venezuela (1982-1997)mentioning
confidence: 99%